ISLAM AND MULTICULTURALISM: CHALLENGE TO THE FUTURE OF DEMOCRACY IN INDONESIA - Saidi, Anas (P2KK LIPI, 2012)
Amids the world’s attention to Indonesia, a question is raised: “will the world’s largest Muslims country be able to show Islamic capabilities with democracy?” Ironically, intolerance based on religious spirits with their violent face has continued to increase. Democratic structure formulated after the demised of the New Order regime in 1998 is now facing a new challenge from the rise of theocracy that opposed democracy, pluralism, and multiculturalism. The rise of theocracy is essentially inconsistent with the “Unity in Diversity” principle. Religious politics struggling to institutionalized this theocracy model has become “the sand in the shoe” in the mids of Indonesia’s celebration of multiculralism and pluralism embracing deliberative democracy. Obstacles to democratic reconciliation occured not only due to disfunction of democratic institutions that concentrate much on democratic procedure instead of substantive democracy; but also has been distorted by these theocracy ideals that continues to emerge. The jargon to uphold Islam as a whole (“kaffah”) stated religious views is un-negotiable, although this is actually in contrast with the Islamic principle, “shalih likulli zaman wa makan” (meaning: religious universality applies accross time and space). The effort to textualized with interpretation, can easily fall into the use of violence has given a negative contribution to the building of democracy. Pancasila as nation’s concensus, a conditio sine quanon, for pluralistic and multiculture Indonesia, has now continued being disputed. Keywords: Islam, multiculturalism, democracy